A 5-year Survey Reveals Increased Susceptibility to Glycopeptides for Methicillin-Resistant Staphylococcus aureus Isolates from Staphylococcus aureus Bacteremia Patients in a Chinese Burn Center - Bei Jiang; Supeng Yin; Bo You; Guangtao Huang; Zichen Yang; Yulong Zhang; Yu Chen; Jing Chen; Zhiqiang Yuan; Xiancai Rao; Xiaomei Hu; Yali Gong; et al. (Frontiers in Microbiology, 2017)
Methicillin-resistant Staphylococcus aureus (MRSA) infections are prevalent in burn wards, and are especially serious in S. aureus bacteremia (SAB) patients. Glycopeptides and daptomycin are effective against MRSA infections, but MIC creeps can reduce their efficacy. Our object was to perform a molecular epidemiological investigation of S. aureus isolates in our burn center and to evaluate MICs for antimicrobials against SAB-associated MRSA isolates. A total of 259 S. aureus isolates, obtained from August 2011 to July 2016, were used in this study. Multiple molecular typing was used for molecular epidemiological analysis. E-tests were used to determine MICs of vancomycin, teicoplanin, and daptomycin for SAB-associated MRSA isolates. MIC values were stratified by collection date or source and compared. Spearman's test was used to analyze MICs correlations amongst tested antimicrobials. ST239-MRSA-III-t030-agrI clone was found to be dominant in both SAB and non-SAB patients, and significantly more in SAB patients (P < 0.0001). SAB-MRSA isolates exhibited decreased MICs for vancomycin, teicoplanin, and daptomycin during the 5-year period. Compared to those isolated from catheters or wounds, SAB-MRSA isolates from the bloodstream were less susceptible to vancomycin and daptomycin, but more susceptible to teicoplanin. MICs Correlation was found only between vancomycin and daptomycin in MRSA isolates from the bloodstream (rho = 0.250, P = 0.024). In conclusion, our results suggest that MRSA infections are still serious problems in burn centers. In contrast to most other studies, we observed increased susceptibility to glycopeptides and daptomycin against SAB-associated MRSA in our center from 2011 to 2016, suggesting the use of glycopeptides does not lead to MIC creeps. Isolates from different sites of the body may exhibit different levels of susceptibility and change trend over time for different antimicrobials, antimicrobials selection for MRSA infections should be considered comprehensively.